The principles of creating a bilingual e-poetical dictionary, as well as similar and different aspects of the means of artistic images in Uzbek and English - Odilova Gulnoza, Djumabayeva Jamila Sharipovna, Mahmudova Maftuna Abdurashidovna (International Journal of Advanced Science and Technology, 2020)
This article deals with the issues based on analyzing the principles of creating a bilingual e-poetical dictionary, as well as similar and different aspects of the means of literary explanation in Uzbek and English. The article presents the dictionary which contains several stages and gave described them with special illustrations.